Parenteral glutamine supplementation improves serum albumin values in surgical cancer patients. Issue 2 (February 2021) - Wu, Jin-Ming; Ho, Te-Wei; Lai, I-Rue; Chen, Chiung-Nien; Lin, Ming-Tsan
Summary: Introduction: Patients with gastric adenocarcinoma (GA) often develop malnutrition, which deteriorates after cancer surgery and negatively affects surgical outcomes. Despite being an abundant and versatile amino acid involved in the immune system and metabolic functions, glutamine levels are significantly depleted among patients who are critically ill or hypercatabolic. Therefore, this study aimed to investigate whether parenteral glutamine supplementation may improve nutritional status and surgical outcomes. Methods: This retrospective, single-center cohort study included patients with GA who underwent gastrectomy between January 2007 and June 2019. Patients were classified into either the non-glutamine or glutamine group. Propensity score matching was used to minimize the bias in patient demographics. Furthermore, the average parenteral glutamine dose from the day of surgery to postoperative day four was calculated in g/kg/day. Surgical outcomes (length of hospitalization, major complication, and mortality) and changes in lymphocyte count and serum albumin levels 7 days post-surgery were assessed in both matched groups using adjusted models. Results: A total of 1950 patients were reviewed, among whom 522 (26.8%) received parenteral glutamine supplementation (glutamine dose ranging from 0.05 to 0.49 g/kg/day). Among the included patients, 57.2% were males, and the median age was 64.9 years. After matching, there were 478 cases in each group. No differences in surgical outcomes and changes in lymphocyte count were observed between both matched groups. The glutamine group exhibited a smaller decrease in serum albumin levels compared to the non-glutamine group (−0.6 vs. −1.1 g/dL; P  < 0.001). The adjusted matched model showed that glutamine dose contributed significantly toward increasing serum albumin levels (coefficient = 0.08 per 0.1 g/day/kg increment in glutamine; 95% confidence interval: 0.04 to 0.10; P  < 0.001). Conclusions: Perioperative parenteral glutamine supplementation had a positive dose-dependent impact on the recovery of serum albumin levels among patients with GA undergoing gastrectomy, implying that glutamine supplementation improved postoperative nutritional suppression and ameliorated stress-associated inflammation. Although glutamine supplementation was not associated with surgical outcomes, further studies should be conducted to evaluate the clinical significance of serum albumin restoration.